Gesetzgeber und Verfasser der Carolina - Mertens, Bernd (Zeitschrift der Savigny-Stiftung für Rechtsgeschichte. Germanistische Abteilung, 2021)
Emperor Charles V and his councils neither initia-ted the penal code named after him ("Carolina") nor influenced its content. Inspired by the Imperial Court, it was a project of the imperial estates, which pushed it forward and led to its success at the Imperial Diets from 1521 to 1532. The work on the content was carried out in committees composed of members of all Curias and in the Imperial Regiment, with trained lawyers dominating. The view that Johann Freiherr von Schwarzenberg played a decisive role in the drafting of the Carolina, which still prevails in literature today, owes its origins to a certain zeitgeist and is in need of correction. Contrary to previous assumptions, Schwarzenberg was most probably not involved in the first Carolina draft at all and not in the second draft in the decisive editorial phase. Instead, the lawyer Sebastian von Rotenhan, who was most probably involved in the first and certainly in the second Carolina draft, and perhaps even later in the revision of 1530, comes more to the fore. Ultimately, the Carolina, like the "Bambergische Halsgerichtsordnung"which served as a model, was a collective work and was understood as such by contemporaries.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Carolina; Emperor Charles V; Johann Freiherr von Schwarzenberg; Penal Code; Sebastian von Rotenhan